ADHD in Lebanese Schools Diagnosis, Assessment, and Treatment - Berri, Hala Mohammed; Al-Hroub, Anies; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This Brief addresses the causes, assessment, and treatment of ADHD in Lebanese schoolchildren. It details how the disorder is currently defined in Lebanese elementary schools and examines schoolteachers' understanding of and conceptions about ADHD across three domains: general knowledge; symptoms and diagnosis; and treatment. This concise volume presents the authors' research into Lebanese schoolteachers' knowledge of ADHD and their ability and readiness to address the psychological and academic needs of their students who have been diagnosed with the disorder. In addition, the Brief explores the teachers' ability to identify ADHD subtypes in relation to a student's gender within the Lebanese context, emphasizing the differing sociocultural expectations in the behaviors of boys and girls. <Topics featured in this Brief include: Current procedures for identifying ADHD in Lebanon. Lebanese teachers' knowledge about ADHD, their misconceptions, and factors that influence their opinions. Biases toward and confusion about disorders on the basis of perceived gender differences. ADHD assessment and implementation strategies for Lebanese special education professionals. Research questions, design, and methods as well as data collection and analysis procedures used in the study. ADHD in Lebanese Schools is an essential resource for researchers, professionals and policymakers, and graduate students in such interrelated fields as school psychology, educational psychology, and social work.
Chapter 1: Introduction to ADHD in Lebanon -- Chapter 2: Assessment, Diagnosis, and Treatment of ADHD in School-Aged Children in Lebanon -- Chapter 3: Researching Teachers Knowledge and Perceptions of ADHD -- Chapter 4: Teachers' Knowledge of ADHD and Perceptions of the Behavior of Individual Students With ADHD in Relation to Gender and Culture -- Chapter 5: Teachers' Understanding of ADHD, Their Conceptions, and Misconceptions in Relation to the Gender of Students with ADHD and Their Training Needs.
Keywords: Developmental psychology; Educational psychology; Child and School Psychology